Dimethylsulfoxide potentiates the nerve conduction–blocking effect of lidocaine without augmentation of the intracellular lidocaine concentration in the giant axon of crayfish in vitro. (12th April 2012) - Yano, Takeshi; Ibusuki, Shoichiro; Takasaki, Mayumi; Tsuneyoshi, Isao
Abstract The purpose of this study was to investigate how dimethylsulfoxide (DMSO) potentiates the blocking action of lidocaine. A giant axon removed from a crayfish was used to investigate nerve conduction and intracellular lidocaine concentration. The maximum values of the differential waveform (dV/dt max) calculated from evoked action potentials were used for evaluating an inhibition of nerve conduction. The inhibition of the dV/dt max in low‐frequency stimulation (tonic block) and high‐frequency stimulation (phasic block) after perfusion of 1 mm lidocaine with or without 0.2 vol % DMSO, in which the concentration of DMSO alone had no anesthetic effect, was measured to evaluate the potentiating action of DMSO. The intracellular lidocaine concentration was measured via a lidocaine‐sensitive glass microelectrode during 30 min of perfusion of 1 mm lidocaine alone or in combination with DMSO. When applied without lidocaine, DMSO caused a dose‐dependent nerve conduction block when used at concentrations >1 vol %. The dV/dt max in the tonic block was significantly decreased when 0.2 vol % DMSO was added to the lidocaine solution (P = 0.004). In the phasic block, there was no significant potentiating action of DMSO. There were no significant differences in the intracellular lidocaine concentrations with or without DMSO. The potentiating effects of DMSO were observed only in the condition of low‐frequency stimulation and were not related to the intracellular lidocaine concentration in the giant axon of crayfish in vitro.